2020
DOI: 10.31579/2690-8794/048
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Boditech iCHROMA Covid-19 IgG antibody assay with the external quality control for UK NIBSC (National Institute of Biological Standards and Control)

Abstract: Background: There is a need for laboratories to participate in EQA schemes to achieve a harmonization of test results and to improve serological testing and research on COVID-19 and SARS-CoV-2. The Boditech iCHROMA point of care immunoassay analyser has a Covid-19 antibody assay for the qualitative determination of IgG antibodies in human whole blood/serum/plasma. The National Institute for Biological Standards and Control (NIBSC) in the United Kingdom has a portfolio of reference and research reagents, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Covid-19 Infected subject (Day 1-100 post infection): Blood samples had been taken from a subject who suffered mild symptoms confirmed by PCR and antigen tests on day 1,2, 3,4,5,6,7,8,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Covid-19 Infected subject (Day 1-100 post infection): Blood samples had been taken from a subject who suffered mild symptoms confirmed by PCR and antigen tests on day 1,2, 3,4,5,6,7,8,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26…”
Section: Methodsmentioning
confidence: 99%
“…The study concluded that there was 100% agreement of the presence of IgG antibodies in the samples to Covid-19 between the Boditech iCHROMA Covid 19 IgG antibody assay method and the Abbot Architect SARS-CoV-2 IgG method (Clinical Sensitivity). In addition, there was 90% agreement in the absence of Covid-19 IgG antibodies in the samples between the Boditech iCHROMA Covid 19 IgG antibody assay and the Abbot Architect SARS-CoV-2 IgG (Clinical Specificity) [12]. In another study, the performance of the Boditech iCHROMA Covid 19 IgG antibody assay was assessed using the NIBSC (National Institute for Biological Standards and Control) reference material.…”
Section: Introductionmentioning
confidence: 99%